Lexician and Oronim Semantics (On the Example of Toponyms of Jizzakh Region) (International Journal of Psychosocial Rehabilitation, 2020)
This article analyzes interesting facts based scientifically about the denomination of hillocks, soys (mount rivers), streamlets, and kutans (sheepfolds) of the “Oykor” mount lying through the area of the Baxmal district.